2003
DOI: 10.1016/s0378-1127(03)00055-0
|View full text |Cite
|
Sign up to set email alerts
|

Climatic controls on fire-induced sediment pulses in Yellowstone National Park and central Idaho: a long-term perspective

Abstract: Fire management addressing postfire erosion and aquatic ecosystems tends to focus on short-term effects persisting up to about a decade after fire. A longer perspective is important in understanding natural variability in postfire erosion and sedimentation, the role of these processes in structuring habitat, and future expectations in light of a warming climate and environmental change. In cool high-elevation forests of northern Yellowstone National Park, stand ages indicate infrequent large stand-replacing fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
85
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(86 citation statements)
references
References 73 publications
1
85
0
Order By: Relevance
“…Millspaugh et al (1998) suggested a trend related primarily to solar insolation, though more detailed dating suggests a link to millennial-scale phenomena (see also Meyer et al 1995). The results of Meyer et al (1995), discussed by Meyer and Pierce (2003), suggest an anti-correlation with Bond cycles and also a response to century-scale events such as the MWP and the Little Ice Age. Meyer and Pierce (2003) also compared the Yellowstone results to those from Idaho (Meyer et al 2001).…”
Section: Discussionmentioning
confidence: 97%
“…Millspaugh et al (1998) suggested a trend related primarily to solar insolation, though more detailed dating suggests a link to millennial-scale phenomena (see also Meyer et al 1995). The results of Meyer et al (1995), discussed by Meyer and Pierce (2003), suggest an anti-correlation with Bond cycles and also a response to century-scale events such as the MWP and the Little Ice Age. Meyer and Pierce (2003) also compared the Yellowstone results to those from Idaho (Meyer et al 2001).…”
Section: Discussionmentioning
confidence: 97%
“…Meyer et al, 2001;Meyer and Pierce, 2003). Identifying confluence environments may therefore depend on the length of time since the last erosion and sediment-transport event, and this may be specific to individual tributary basins.…”
Section: Symmetry Ratios and Confluence Environmentsmentioning
confidence: 99%
“…Here we provide a millennial-scale, high-resolution history of middle-elevation forests where there are concerns about unnaturally high fuel loads and altered fire regimes. Few sediment-based studies have evaluated fire severity (i.e., tree mortality and soil impacts), although there is a potential to reconstruct geomorphic responses to severe fire from signatures in colluvial and alluvial sediment (24). In this study we present a paleoecological record of the last 2,000 y of fire, erosion, and vegetation changes in the dry mixed-conifer/broadleaved evergreen zone of the Siskiyou Mountains to examine (i) the variability of fire during the climatic changes of the Medieval Climatic Anomaly (MCA; ca.…”
mentioning
confidence: 99%